Pengaruh Brand Ambassador dan Celebrity Endorser Terhadap Minat Beli Produk Skintific - Fevi Aprianti; Diandra, Didip (JURNAL MANAJEMEN MOTIVASI, 2026)
This study analyzes the influence of Celebrity Endorsers and Brand Ambassadors on purchase interest in Skintific products. Using a quantitative survey method with 286 purposively selected respondents, data were collected via questionnaires and literature reviews. SPSS analysis shows both variables have a positive and significant effect on purchase interest. The R² value of 0.302 indicates that Brand Ambassadors explain 30.2% of the variance. Findings suggest that public figures significantly shape brand perception, and future studies may benefit from mixed methods to explore consumer-brand relationships more comprehensively.